Facile fabrication and electrochemical oxidation of activated carbon microtube bundles for advanced all-solid-state supercapacitors. (6th July 2020) - Bao, Jinpeng; Lu, Haiyan; Pei, Dongyu; Liang, Chen; Chen, Yang
Abstract: The energy density of carbon microtube bundles (CMTBs) is usually low and the preparation process is complex. After carbonization, washing and activation, the prepared metaplexis shell-based carbon microtube bundles (MS-CMTBs) not only have an open structure, but also a rich porous structure on the tube wall. The pulsed electrooxidation technology can promote the formation of functional groups on the tube wall and further enhance the energy density of the material. After assembling the electrooxidized material into an all-solid-state supercapacitor, the capacitor has a capacity of 15.1 Wh kg −1 at 0.5 A g −1 and a capacity retention rate of 95.9% after 10 000 cycles at 10 A g −1, indicating that these functional groups are relatively stable. The result shows that the MS-CMTBs before pulsed electrooxidation are more suitable as positive electrode materials, while the electrooxidized material can be either a positive or negative electrode material. This work provides an idea for the design and development of electrode materials in high-performance all-solid-state supercapacitors.